2017
DOI: 10.1051/epjconf/201713711004
|View full text |Cite
|
Sign up to set email alerts
|

The Parameters of The Tsallis Distribution at the LHC

Abstract: Abstract. This talk focuses on fits, using the Tsallis distribution, extending to very large values of the transverse momentum of charged particles in p-p collisions and on the energy dependence of the parameters. A thermodynamically consistent form of the distribution is used for fitting the transverse momentum spectra at mid-rapidity. The fits based on the proposed distribution provide a very good description over 14 orders of magnitude. The parameters obtained show a smooth increase in the value of q and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…With (32) and the parametrizations of the Tsallis -Pareto parameters above, (29)- (31) we can calculate the yield of a given hadron species at any center-of-mass energy and centrality, using the corresponding number of participant nucleons, N part , taken from experimental data. The integrated yields per unit rapidity for various identified hadrons stemming from √ s N N = 2.76 TeV PbPb collisions with different centrality classes measured by ALICE are shown on figure 5a with red circles, the most central data located on the top [57,58,72,74,75].…”
Section: Multiplicity Scalingmentioning
confidence: 99%
“…With (32) and the parametrizations of the Tsallis -Pareto parameters above, (29)- (31) we can calculate the yield of a given hadron species at any center-of-mass energy and centrality, using the corresponding number of participant nucleons, N part , taken from experimental data. The integrated yields per unit rapidity for various identified hadrons stemming from √ s N N = 2.76 TeV PbPb collisions with different centrality classes measured by ALICE are shown on figure 5a with red circles, the most central data located on the top [57,58,72,74,75].…”
Section: Multiplicity Scalingmentioning
confidence: 99%
“…The value of q − 1 > 0 is small in many cases [27]. Therefore, the range of q was 1.0 ≤ q ≤ 1.1 in the numerical calculations.…”
Section: Numerical Estimationmentioning
confidence: 99%
“…The values of the parameters were adopted by referring the results in high energy collisions. The value of q − 1 > 0 is small in many cases [27]. Therefore, the range of q was 1.0 ≤ q ≤ 1.1 in the numerical calculations.…”
Section: Numerical Estimationmentioning
confidence: 99%
“…Power-like distributions have been used to describe momentum distributions in high energy collisions. Many researchers have studied momentum distributions, and have used Tsallis-type distributions [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. It has been reported that Tsallis-type distributions describe well momentum distributions.…”
Section: Introductionmentioning
confidence: 99%